Mengelola Batas dalam Konseling: Standar Menerima Hadiah - Aniyatussaidah Aniyatussaidah; H K Marjo (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to describe the explanation of gifts in counseling based on ethical and cultural considerations. The method in this research is a literature study, namely by collecting reading material from various scientific articles and then comparing theories and research results, which are then analyzed descriptively. Based on the results of a literature study conducted that counselors can receive gifts from counselees by considering aspects of culture, time of giving, and types of gifts given.